Mutation Analysis of HTRA2 Gene in Chinese Familial Essential Tremor and Familial Parkinson's Disease. (24th January 2017) - He, Ya-Chao; Huang, Pei; Li, Qiong-Qiong; Sun, Qian; Li, Dun-Hui; Wang, Tian; Shen, Jun-Yi; Du, Juan-Juan; Cui, Shi-Shuang; Gao, Chao; Fu, Rao; Chen, Sheng-Di
Abstract : Background . HTRA2 has already been nominated as PARK13 which may cause Parkinson's disease, though there are still discrepancies among these results. Recently, Gulsuner et al.'s study found that HTRA2 p.G399S is responsible for hereditary essential tremor and homozygotes of this allele develop Parkinson's disease by examining a six-generation family segregating essential tremor and essential tremor coexisting with Parkinson's disease. We performed this study to validate the condition of HTRA2 gene in Chinese familial essential tremor and familial Parkinson's disease patients, especially essential tremor. Methods . We directly sequenced all eight exons, exon-intron boundaries, and part of the introns in 101 familial essential tremor patients, 105 familial Parkinson's disease patients, and 100 healthy controls. Results . No exonic variant was identified, while one exon-intron boundary variant (rs2241028) and one intron variant (rs2241027) were detected, both with no clinical significance and uncertain function. There was no difference in allele, genotype, and haplotype between groups. Conclusions . HTRA2 exonic variant might be rare among Chinese Parkinson's disease and essential tremor patients with family history, and HTRA2 may not be the cause of familial Parkinson's disease and essential tremor in China.